Identificação de regiões com variação no número de cópias de segmentos de DNA em bovinos de raças autóctones espanholas - Silva, Thiago Bruno Ribeiro da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Copy number variation (CNV) are DNA segments that are present at variable copy number compared to a reference genome. Classes of CNVs include insertions, deletions, duplications and inversions. CNVs can be associated with gene expression and phenotypic variation, providing genetic variability among individuals and, thus, are an important tool to production and healthy traits selection. The goal of this study was to identify regions with copy number variation in a total of 366 individuals from 5 autochthonous Spanish breeds of beef cattle, distributed into 25 families for breed, composed of sire-dam-offspring, called trios. The animals belonged to Asturiana de los Valles (75 individuals, 25 trios), Avileña-Negra Ibérica (74 individuals, 24 complete trios, one sire-repeated trio), Morucha (Mo, 75 individuals, 25 trios), Pirenaica (74 individuals, 24 24 complete trios, one sire-repeated trio) e Retinta (68 individuals, 18 complete trios, 7 sire-repeated trios) and were genotyped with the Illumina BovineHD Beadchip. The PennCNV software performed the CNVs identification. The CNV regions (CNVR) were determined by the overlapping of the CNVs. Candidates genes placed within the found CNVRs were investigated by analysis into the NCBI and Ensembl data platform. It has been detected a total of 8,061 CNV, which 2852 are gain and 5592 are loss of a DNA segment. A great amount of sharing CNVs between Asturiana de los Valles and Morucha breeds had been observed, which suggests a proximity during their formation process. We found also 1,293 regions of CNVs, spanning 3.6% of the autosomal bovine genome and 1,263 genes were present within these regions, and were involved in biological processes such as growth and immune system

CNVs (copy number variation - variação no número de cópias) são segmentos de DNA de tamanho igual ou maior a 1 Kb e estão presentes em número variável de cópias em comparação com um genoma referência e podem estar associadas com a expressão gênica e variâncias fenotípicas. Assim, esse trabalho teve como objetivo identificar regiões com variações no número de cópias nos segmentos de DNA em um total de 366 indivíduos de 5 raças bovinas autóctones de corte espanholas, distribuídos em 25 famílias formadas por pai-mãe-progênie, denominados trios. Os animais pertencentes às raças Asturiana de los Valles (75 indivíduos, 25 trios), Avileña-Negra Ibérica (74 indivíduos, 24 trios completos, um trio com pai repetido), Morucha (Mo, 75 indivíduos, 25 trios), Pirenaica (74 indivíduos, 24 trios completos, um trio com pai repetido) e Retinta (68 indivíduos, 18 trios completos, 7 trios com pais repetidos) foram genotipados com o painel Illumina BovineHD Beadchip de 777K A identificação das CNVs foi realizada por meio do modelo das cadeias ocultas de Markov implementado no software PennCNV. As regiões de CNV (copy number variation region - CNVR) foram determinadas pela sobreposição de agrupamentos das CNVs identificados em diferentes animais. Genes candidatos localizados nas CNVR encontradas foram investigados por meio de análises nas plataformas NCBI e Ensembl. Foram detectadas 8061 CNVs, sendo 2852 cópias e 5592 deleções e 1293 regiões, sendo 876 deleções e 314 cópias, cobrindo 3,6% do genoma autossômico bovino. Foram encontrados dentro dessas regiões 1.263 genes, com alguns deles fazendo parte de processos biológicos como crescimento e sistema imune. Encontrou-se um grande número de CNVs sendo compartilhadas entre as raças Asturiana de los Valles e Morucha, o que sugere proximidade entre essas raças durante seu...
Keywords: Bovino de corte; Genômica; Polimorfismo (Genetica); DNA; Nucleotídeos; Genetica animal; Genomics